A humidity sensor based on quartz crystal microbalance using graphene oxide as a sensitive layer. (June 2017) - Jin, Hao; Tao, Xiang; Feng, Bin; Yu, Liyang; Wang, Demiao; Dong, Shurong; Luo, Jikui
Abstract: Humidity is a vital physical quantity which is extremely important to production quality control, reliability of electronics, and health of human being. This paper proposed a humidity sensor based on quartz crystal microbalance (QCM) using graphene oxide as a sensitive layer, and investigated the characteristics of sensor according to the shift of quality factor (Q factor) as well as resonant frequency at different relative humidity (RH). Results show that at low RH values, the shift of Q factor is more suitable than the shift of resonant frequency for assessing the sensitivity of the sensor. By combining both frequency and Q factor shifts, we obtain a sensitivity of ∼1371/1%RH at 10–60%RH (by Q factor) and 1068 Hz/10%RH at 70%RH (by frequency), which are much better than the reported QCM humidity sensors, with good linearity. The QCM humidity sensor also shows good repeatability with response time and recovery time smaller than 20 and 3 s, respectively. These good characteristics of the sensor are attributed to the large surface area and high hydrophilic nature of the graphene oxide, demonstrated good potential for future applications. Highlights: A humidity sensor based on quartz crystal and graphene oxide is proposed. Characteristics are studied by both the shift of Q factor and resonant frequency. Sensitivity by shift of Q factor is more suitable for low relative humidity.